Inovasi Pembuatan Alat Produksi Gelar Kain Untuk Mempermudah Produksi Konveksi di Kecamatan Kadungora - rudi, Rudi; Purwanda, Eka (Jurnal Online Manajemen ELPEI, 2025)
This study aims to analyze the impact of innovation in the manufacture of cloth title production tools on the efficiency, quality, and competitiveness of the convection industry in Kadungora District. This innovation focuses on the development of tools that can accelerate the production process, increase product precision, and reduce production costs. The results of the study indicate that the implementation of new cloth title production tools increases production efficiency by 30%, which allows convection companies to increase output without significantly increasing resources. In addition, the increased precision of this tool produces more consistent products, increases customer satisfaction, and strengthens the company's reputation. The 20% reduction in production costs also gives the company a competitive advantage in the market, with high-quality products that can be offered at more competitive prices. The positive impact of this innovation is not only seen in the operational aspects of the company, but also in increasing industry competitiveness and local economic growth. Thus, this study emphasizes the importance of adopting technology and innovation to drive the progress of the convection industry and economy in Kadungora District